Attractive In Situ Self‐Reconstructed Hierarchical Gradient Structure of Metallic Glass for High Efficiency and Remarkable Stability in Catalytic Performance. (8th February 2019) - Jia, Zhe; Wang, Qing; Sun, Ligang; Wang, Qi; Zhang, Lai‐Chang; Wu, Ge; Luan, Jun‐Hua; Jiao, Zeng‐Bao; Wang, Anding; Liang, Shun‐Xing; Gu, Meng; Lu, Jian
Abstract: Metallic glass (MG), with the superiorities of unique disordered atomic structure and intrinsic chemical heterogeneity, is a new promising and competitive member in the family of environmental catalysts. However, what is at stake for MG catalysts is that their high catalytic efficiency is always accompanied by low stability and the disordered atomic configurations, as well as the structural evolution, related to catalytic performance, which raises a primary obstacle for their widespread applications. Herein, a non‐noble and multicomponent Fe83 Si2 B11 P3 C1 MG catalyst that presents a fascinating catalytic efficiency while maintaining remarkable stability for wastewater remediation is developed. Results indicate that the excellent efficiency of the MG catalysts is ascribed to a unique atomic coordination that causes an electronic delocalization with an enhanced electron transfer. More importantly, the in situ self‐reconstructed hierarchical gradient structure, which comprises a top porous sponge layer and a thin amorphous oxide interfacial layer encapsulating the MG surface, provides matrix protection together with high permeability and more active sites. This work uncovers a new strategy for designing high‐performance non‐noble metallic catalysts with respect to structural evolution and alteration of electronic properties, establishing a solid foundation in widespread catalytic applications. Abstract : Fe‐based metallic glass catalysts with a disordered atomic structure are prepared by a melt‐spinning technique. The metallic glass catalysts present excellent catalytic performance in both efficiency and stability when compared to the state of the art. The high catalytic efficiency is due to their intrinsic formation of metallic bonds and electronic delocalization, while the superior catalytic stability is owing to their self‐reconstruction ability.